Tonometer calibration in Brasília, Brazil - Abrão,Fernanda Pires da Silva (2009)
PURPOSE: To determine calibration errors of Goldmann applanation tonometers in ophthalmic clinics of Brasília, Brazil, and correlate the findings with variables related to tonometers model and utilization. METHODS: Tonometers from ophthalmic clinics in Brasília, Brazil, were checked for calibration errors. A standard Goldmann applanation tonometer checking tool was used to asses the calibration error. Only one trained individual made all verifications, with a masked reading of the results. Data on the model, age, daily use, frequency of calibration checking and the nature of the ophthalmic department - private or public - were collected and correlated with the observed errors. RESULTS: One hundred tonometers were checked for calibration. Forty seven percent (47/100) were out of 1 mmHg range at least at one point checking. Tonometers mounted to slit lamp, with less than 5 years, used in less than 20 patients daily, that had a calibration check on a yearly basis, and those from private office exhibit a lower rate of inaccuracy, but only the first variable was statistically significant. Sixty one percent of tonometers on public hospitals were out of calibration. CONCLUSION: Calibration of tonometers in the capital of Brazil is poor; those from general hospitals are worst, and this fact can lead to inaccurate detection and assessment of glaucoma patients, overall in the population under government assistance.